ELEMENTAL CONCENTRATIONS AND SOIL-TO-MOSS TRANSFER FACTORS OF RADIONUCLIDES IN THE ENVIRONMENT OF NORTH KOSOVO AND METOHIJA - Gulan, Ljiljana; Jakšić, Tatjana; Milenković, Biljana; Stajić, Jelena (Bulletin of Natural Sciences Research, 2020)
This paper deals with investigations of elemental concentrations and soil-to-moss transfer factors of radionuclides in area of municipalities Kosovska Mitrovica and Zubin Potok. Twelve samples of soil and moss Hypnum cupressiforme Hedw. were collected during May 2018. Transfer factors of radionuclides: 226Ra, 232Th, 40Kand 137Cs were calculated with regard to elemental concentrations of radionuclides in soil and moss samples. Analysis was done in order to indicate the different ways of adopting radionuclides by mosses. According to calculated transfer factors and analysis, authors concluded that the soil is dominant source of natural radionuclides and their concentration in moss occurred due to resuspension of soil particles, while artificial 137Cs is present in soil and moss samples as a consequence of atmospheric dry and wet deposition.
Keywords: Elemental concentration; Transfer factor; Radionuclide; Moss; Soil